The moderating role of hair cortisol in the association of early and recent stress with stress-related phenotypes - Torrecilla, Pilar; Barrantes-Vidal, Neus (Frontiers in Psychology, 2023)
Background: Increased hair cortisol concentrations (HCC) have been found in clinical samples of schizophrenia, first episode psychosis and clinical risk for psychosis, but evidence of such is scarce in schizotypy. High HCC are supposed to reflect elevated chronic stress. However, HCC were not directly associated with adversity measures and stress-related phenotypes in previous research. This study tested whether HCC moderated the association between a comprehensive range of psychosocial stressors with several stress-related phenotypes in a sample of nonclinical young adults. It was expected that stressors, either distal (i.e., early-life) or recent, would be associated with to subclinical features in the context of elevated biological sensitization to stress (i.e., elevated HCC). Methods: The sample comprised 132 nonclinical young adults belonging to the Barcelona Longitudinal Investigation of Schizotypy Study (BLISS). Participants completed a questionnaire of childhood adversity and two complementary measures of recent life events, tapping threatening versus more general life events. Both the frequency and subjective impact (positive versus negative) of general life events were also assessed. Psychotic (i.e., schizotypy, suspiciousness) and non-psychotic (i.e., depression, anxiety) subclinical features as well as appraisals of perceived stress were examined. Hierarchical linear regressions and simple slope analyses were computed. Results: HCC moderated the effects of both early and recent stress on suspiciousness as well as the effects of recent life events on perceived stress, such that those with higher HCC presented increased suspiciousness and perceived stress at higher levels of stress exposure. Positive, but not negative, recent life events were associated with decreased perceived stress and depression, and these associations were moderated by low HCC, indicating a buffering effect for those with a non-impaired HPA axis. Conclusions: In line with the neural diathesis-stress model, results highlight the role of the interplay between the HPA axis and exposure to stressful experiences in exacerbating psychosis features and extend evidence to the nonclinical expression of the psychosis continuum. In addition, findings support the protective effect of positive experiences in decreasing stress appraisals and affective disturbances, which is consistent with emerging research about the relevance of positive factors in reducing the likelihood of psychopathological outcomes.